Complexos metálicos como ligantes: síntese e estudo das propriedades de magnetos moleculares contendo paládio (II) - Willian Xerxes Coelho Oliveira (2013)
This work describes the synthesis and structural characterization of eight new coordination compounds, five of them being building blocks containing palladium(II) and three of them molecular magnets derivate. The building blocks are metal complexes based on proligands opba (1,2-phenylenebis(oxamato)) and mpba (1,3-phenylenebis(oxamato)): K2[Pd(opba)].2H2O, K4[Pd2(mpba)2].4H2O, (PPh4)2[Pd(opba)], [Pd(NH3)4][Pd(opba)] and K4[Pd2(mpba)2].H2O.dmso (in which PPh4+ is the tetraphenylphosphonium cation and dmso is dimethylsulfoxide). The crystal structures of the last three compounds were elucidated by single crystal X-ray diffraction, and consist in the first examples of palladium(II) complexes containing oxamate ligands fully deprotonated. The clusters [Cu(bpca)]2[Pd(opba)].z2dmso and [Cu(bpca)]4[Pd2(mpba)2].6H2O (bpca = bis(2-pyridilcarbonil)amidate anion) and coordination polymer [Co(H2O)2{Pd(opba)}]nn dmso had their crystal structures determined by single crystal X-ray diffraction. The coordination polymer presented an evidence of single-crystal-to-single-crystal phase transition at 177 K. The study of magnetic properties of building blocks revealed that [Pd(opba)]2- and [Pd2(mpba)2]2- anions are diamagnetic, which is in agreement of the square planar geometry of palladium(II) ions. The magnetic measurements of clusters and coordination polymer showed that the spin carrier units copper(II) or cobalt(II) are magnetically isolated due to the presence of palladium(II) between them. The clusters as well as the coordination polymer are paramagnetic at room temperature and exhibit antiferromagnetic coupling at low temperatures.